2022
DOI: 10.3389/fpubh.2022.867626
|View full text |Cite|
|
Sign up to set email alerts
|

“For me, it's just a piece of freedom”—Increased empowerment through physical activity promotion among socially disadvantaged women

Abstract: IntroductionCommunity-based participatory research (CBPR) is an effective health promotion approach for reaching socially disadvantaged groups. However, there is limited evidence on how such interventions and their effects can be reproduced across time and place. The present study examines the effects of BIG (i.e., movement as an investment in health), a long-standing German CBPR project. Since 2005, BIG has aimed to empower women in difficult life situations to increase control over their health determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…This empowerment manifests as increased self-efficacy and self-confidence ( 35 , 36 ). Sauter et al ( 37 ) analyzed qualitative interviews conducted at five BIG sites between 2007 and 2011 and confirmed the positive effects on their individual empowerment (e.g., expansion of their social network and increased integration of PA into their daily lives). They also emphasized the impact on women's organizational (e. g., communicating their desires and requirements to others) and community empowerment (e.g., developing advanced problem-solving skills) ( 37 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This empowerment manifests as increased self-efficacy and self-confidence ( 35 , 36 ). Sauter et al ( 37 ) analyzed qualitative interviews conducted at five BIG sites between 2007 and 2011 and confirmed the positive effects on their individual empowerment (e.g., expansion of their social network and increased integration of PA into their daily lives). They also emphasized the impact on women's organizational (e. g., communicating their desires and requirements to others) and community empowerment (e.g., developing advanced problem-solving skills) ( 37 ).…”
Section: Discussionmentioning
confidence: 89%
“…They also emphasized the impact on women's organizational (e. g., communicating their desires and requirements to others) and community empowerment (e.g., developing advanced problem-solving skills) ( 37 ). The transferability of the BIG approach was observed among the examined communities ( 37 ). Furthermore, quantitative data collected at two BIG sites between 2006 and 2013 reported improved health status and increased PA among participating women compared to before BIG participation ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they may be vulnerable to other human rights abuses and suffer poor health outcomes [ 25 ]. Research has shown that women empowerment programs have contributed to women’s increased motivation to change physical activity behavior [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we refer to these considerations and to “empowerment outcomes on the individual” level and “empowering processes on the organizational and community levels” ( 39 ). Our approach has been used in previous studies examining the empowerment of socially disadvantaged women through their participation in PA promotion ( 43 , 44 ).…”
Section: Introductionmentioning
confidence: 99%